Scale bar errors of cold-water coral 3D reconstructions from three different setups - Alvaro Romo; Cristina Gutiérrez-Zárate; Meri Bilan; Andrea Gori; Alfredo Veiga; Rodrigo Pérez; Maria Rakka; António Godinho; Timm Schoening; Andrew G Jr Carey; Marina Carreiro-Silva; Covadonga Orejas (PANGAEA, 2025)
For accurate 3D photogrammetric measurements of corals under laboratory conditions, two prototypes (Azores 3D system and Barcelona 3D system) and a final setup (Coruña 3D system) were presented. These setups were designed to obtain a complete set of images of a coral in an aquarium and create accurate 3D reconstructions. A total of 24 (Azores), 177 (Barcelona) and 120 (Coruña) 3D reconstructions of cold-water corals were used to evaluate the systems. The effectiveness of the three systems was assessed by taking into account the total scale error of the 3D reconstructions. The total scale error is the difference between the input scale bar lengths and the measured distance between two-point markers. Here, we provide the total scale error from every reconstruction of each system.